1976
DOI: 10.1128/aac.10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of Ceftezole, a New Cephalosporin Derivative

Abstract: Ceftezole, a new cephalosporin derivative, was compared with cefazolin, cephaloridine, and cephalothin. Data obtained indicate that it is a broad-spectrum antibiotic, with almost identical antimicrobial activity against pathogenic organisms isolated from patients. The therapeutic effect of ceftezole on experimental infections in mice was similar to that of cefazolin and was superior to that of cephalothin. The binding of ceftezole to serum proteins was somewhat less than that of cefazolin. The concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 0 publications
2
49
0
Order By: Relevance
“…The antibacterial activity of FK 749 against clinical isolates was compared with that of SCF 963, Sodium(6R,7R)-7-[(Z)-2-methoxyiminc-2-(2-aminothiazole-4-yl)acetamidol-8-oxo-5-thia-I-a abicyclo [4,2,0] and were somewhat inferior to SCE 963 and cefmetazole (mean: 1.37 and 1.78 pg/ml, respectively).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The antibacterial activity of FK 749 against clinical isolates was compared with that of SCF 963, Sodium(6R,7R)-7-[(Z)-2-methoxyiminc-2-(2-aminothiazole-4-yl)acetamidol-8-oxo-5-thia-I-a abicyclo [4,2,0] and were somewhat inferior to SCE 963 and cefmetazole (mean: 1.37 and 1.78 pg/ml, respectively).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…It was synthesized and studied extensively in Japan (6, 11-13, 16) before being developed for clinical use in the United States. Pharmacokinetic studies in normal subjects have shown higher and more prolonged serum levels with cefazolin than with other cephalosporin antibiotics, e.g., cephaloridine and cephalothin (3,11,16,17). While the drugs were under clinical investigation at Smith Kline & French Laboratories, a series of studies were undertaken to obtain additional human pharmacology data on cefazolin and compare it with cephalothin (2).…”
mentioning
confidence: 99%
“…1, 3 The serum half-life of cefazolin was reported to be approximately 2 hours for the intramuscular route. 1,17,18 For the intravenous route, it was slightly shorter, approximately 1.5 hours, compared with the intramuscular route (Fig.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…A total of 74%-86% of cefazolin is bound to serum proteins. 3,23 Approximately 90% of cefazolin sodium is excreted in the urine as unchanged drug and is minimally metabolized in the liver. 3,24 Recommended dosage and dosage intervals based on pharmacokinetics and pharmacodynamics (Pk-PD) concepts…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation